Family legal relations in the context of gender equality: Legal protection of women and men - Olena Ivanii (Правові горизонти, 2025)
Gender equality in family legal relations remains a critically important topic in contemporary legal discourse, as traditional patriarchal models continue to influence judicial practice and social norms, despite legislative progress. In Ukraine and other countries, systemic issues persist: discrimination in child custody cases, unequal distribution of marital property, and insufficient effectiveness of domestic violence protection mechanisms. Research reveals a significant gap between formal equality guarantees and their practical implementation, exacerbated by socio-cultural stereotypes and institutional biases. The study is particularly relevant due to Ukraine’s European integration processes and the need to harmonize national legislation with European standards. The article aims to provide a comprehensive analysis of family legal relations with a gender perspective, particularly in marriage, divorce, parenthood, custody, and property relations. The study seeks to identify systemic inequalities in the protection of women’s and men’s rights, assess the effectiveness of existing legal mechanisms, and develop recommendations for legislative improvement. An important aspect is the analysis of international experience (e.g., Sweden’s parental leave system, Estonia’s joint custody model, German family courts) to adapt best practices in Ukraine. The study employs a combination of methods: legal analysis of Ukrainian and international legislation (Constitution of Ukraine, Family Code, CEDAW, Istanbul Convention). Comparative legal method to assess EU approaches (Poland, Estonia, Germany, Sweden, Italy). Sociological analysis of statistical data (domestic violence rates, custody case rulings) and social survey results. Systematic and formal-logical methods to interpret legal norms in a socio-cultural context and identify contradictions. Inequality in law enforcement: despite legislative equality guarantees, 68% of real estate is registered under men’s names, and in 70% of custody cases, courts award children to mothers. Judicial stereotypes: Only 15% of custody rulings favor fathers, reflecting conservative judicial approaches. Combating domestic violence: Only 8% of domestic violence cases result in convictions, and protective orders are often unenforced. International experience: Sweden (96% of men take parental leave), Estonia (electronic monitoring for aggressors), and Germany (joint custody) offer effective models for Ukraine. The impact of gender quotas in the judiciary on family dispute resolution. Economic incentives for shared parenting (tax benefits, subsidies). Educational programs on gender equality to counter stereotypes. Comparative analysis of post-Soviet countries’ family law practices. The study demonstrates the need for systemic changes combining legislative reforms, improved law enforcement, and social awareness to achieve genuine gender equality in family relations.